Evaluating the protective effects of mouthguards with neutralizing agents against chlorinated water-induced enamel erosion - Kemporn Kitsahawong; Waranuch Pitiphat; Pawin Thongpaiboon; Sasitorn Thongpaiboon; Sutthiphon Saengsuwannarot (Frontiers Media S.A., 2024)
IntroductionDental erosion is a common problem among swimmers. This study evaluated the effects of mouthguard use with or without neutralizing agents, compared to no mouthguard use, on the microhardness of dental enamel after a swimming simulation.MethodsNinety-six human premolars were randomly allocated into six groups of 16 each: Group A (no mouthguard), Group B (mouthguard only), Group C (mouthguard with fluoride toothpaste), Group D (mouthguard with fluoride-free toothpaste), Group E (mouthguard with CPP-ACP), and Group F (mouthguard with arginine-fluoride toothpaste). Enamel slabs were fixed in a wax model (Typodont Articulator) and used to fabricate mouthguards for all groups except Group A. Each specimen underwent cyclic immersion: 2 h in acidic chlorinated water (pH 3.1) followed by 22 h in artificial saliva, for 28 days, to simulate swimming exposure. The change in enamel surface hardness was measured using a Vickers hardness tester. All groups underwent microhardness testing, scanning electron microscopy, and polarized light microscopy.ResultsThe enamel hardness significantly decreased in all groups after the swimming simulation (paired t-test, P-values < 0.001), except for Group F, which used a mouthguard with arginine-fluoride toothpaste [mean reduction: 17.9 kg/mm2, 95% confidence interval (CI): −1.9, 37.7, P-value = 0.07]. Group A, without a mouthguard, exhibited the highest reduction in enamel surface hardness (mean: 190.6 kg/mm2; 95%CI: 177.4, 203.9), significantly differing from all other groups with mouthguards (P-values < 0.001). However, no statistically significant differences were observed in enamel hardness reduction among the mouthguard groups. SEM micrographs illustrated rough, irregular erosion patterns and several deep porous areas on enamel surfaces of Group A. In contrast, all mouthguard groups showed enamel surfaces similar to sound tooth surfaces. A polarized light microscopic study revealed the deepest dark areas on the enamel surface of Group A.ConclusionsMouthguards significantly reduced enamel microhardness loss compared to no mouthguard use. While no significant differences were found among mouthguard groups with or without neutralizing agents, those lined with arginine-fluoride toothpaste showed the least enamel loss, suggesting its potential protective effect. Within the limitations of this in vitro study, further clinical trials are needed to validate these results.